Analysis Of Multiple Regression Data Mining Methods On The Prediction Of Ibtidaiyah School Registration - Fica Oktavia Lusiana (Yayasan Kita Menulis, 2022)
Data mining originates from data explosion problems experienced by agencies / companies that have collected data from various kinds of transactions. Data mining is the process of looking for patterns or interesting information in selected data using certain techniques or methods. Techniques, methods, or algorithms in data mining vary widely. The choice of the right method or algorithm is very much dependent on the objectives and the overall Knowledge Discovery in Database (KDD) process. The algorithm used in this research is Multiple Linear Regression. School is a suitable place for the application of this method, therefore this research was conducted at the Madrasah Ibtidaiyah Sinaksak Foundation School. The purpose of this study, among others, was to determine the number of registrants at the Madrasah Ibtidaiyah Foundation School (YMI) Sinaksak. In this study, researchers used multiple linear regression association data mining methods. Sources of research data used are observation and interview methods. It is hoped that from the research the school can make a decision or strategy in the estimation of registrants in the following year.